Fall of the absurd. Nostalgia a defence against the absurdity of the characters of Albert Camus and Jerome Ferrari - Hafi, Meriem (Journal of Human Sciences, 2020)
In this article, we present an analysis that brings together the writing of two contemporary writers: Albert Camus and Jerome Ferrari. We begin by defining the two concepts of the absurd and nostalgia, and we explain later how nostalgia could be a remedy for absurdity by highlighting its role in the moral support of the characters in the periods of decline.